California County Planning Commissioners Conference at Fresno Airport Holiday Inn - Watkins, Howard::::::::: (1982)
Entertainment by Good Company Players' Junior Company: Front row: Ann Lyles, Barry Ramalho, Steffi Takahaski, Alison McDonald, Lara Ramalho